The Criminal Procedure (Identification) Act, 2022: A Critical Appraisal in the Light of Right to Equality & Privacy (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
On April 4 and 6, Lok Sabha and Rajya Sabha had respectively passed the Criminal Procedure(Identification) Bill, 2022 following a lengthy debate. With the President giving his assent to the Bill on April 18, it was duly notified by the Government, bringing the Act into force. It is a modification of the Identification of Prisoners Act, 1920, which stands repealed through Section 10(1) of the 2022 Act. In entirety, there has been considerable evolution as compared to the previous 1920 Act which is a colonial law that permitted the collection of fingerprints, footprint impressions, and photographs of convicts and others. The Criminal Procedure (Identification) Act, 2022 was enacted with the aim of authorizing law enforcement agencies to take measurements of convicts and other persons for the purposes of identification and investigation in criminal matters. It is essential to note that the 2022 Act is digitalizing the criminal records and paving the way to make data with respect to criminals easily available through a centralized database, thereby being in accordance with the global standards adopted by various other countries. The Act widens the power of State and its enforcement agencies during a criminal investigation, with regard to the taking of biometric and other biological data of any person arrested by the police, including persons detained under preventive detention laws. While the term ‘any person’ doesn’t specify exactly who are to come under the purview of this Act, it widens the scope of its application, leaving it to the whims and fancies of the State and its enforcement agencies. The author intends to analyse the Act’s potential misuse and possible intrusion into the ambit of fundamental rights such as the right to equality and privacy of those covered by the Act. Further, the author wishes to provide a concise explanation of the Act and numerous other related issues.